RELATIONSHIP BETWEEN INTELLECTUAL INTELLIGENCE, ADVERSITY QUOTIENT AND EMPLOYEE PERFORMANCE MEDIATED BY RELIGIOUSITY - Bachmid, Sofyan; Harun, Harun; Noval, Noval (Jurnal Riset Bisnis dan Manajemen, 2023)
This article presents a novel approach to understanding the relationship between intellectual intelligence, Adversity Quotient, religiosity, and employee performance in Islamic banks. While previous research has focused on examining the individual impact of these variables on employee performance, this study explores the potential mediating effects of religiosity. The study was conducted on a sample of 141 employees at Islamic banks in Palu City, and the data were analyzed using PLS-SEM. The findings indicate that religiosity mediated the relationship between Adversity Quotient and employee performance, while the relationship between intellectual intelligence and employee performance was not mediated by religiosity. These unique findings highlight the importance for Islamic banks to provide worship facilities and hold Islamic studies to enhance employee religiosity, ultimately leading to improved performance. Overall, this study adds novelty to the literature by offering a fresh perspective on the dynamics of employee performance in the Islamic banking sector.